1974
DOI: 10.1084/jem.140.3.631
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of C-Reactive Protein With the Complement System

Abstract: Protamine sulfate was found to consume large amounts of C selectively during preincubation with sera of individuals in the "acute phase". Marked depletion of C1, C4, and C2 with minimal, if any, depletion of C3-9, was observed. The consumption was time and temperature dependent, occurring most rapidly and extensively at 37°C, 0.10 M relative salt concentration and pH 7.5–8.0; it required calcium ions. It was mediated by a heat-stable nondialyzable factor which separated with C-reactive protein (CRP) during fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0

Year Published

1976
1976
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(69 citation statements)
references
References 29 publications
(23 reference statements)
3
66
0
Order By: Relevance
“…One of the first identified properties of native CRP was its ability to activate the complement cascade by sequestration of C1q. In previous studies on CRP-complement interactions, indirect techniques, such as hemolytic activity [14,15], enzyme immunoassays [37] or immunohistochemistry [38] have been used. In the present study, we chose null ellipsometry to analyze the CRP-mediated complement deposition onto model PC-surfaces, a method that is direct, non-destructive, quantitative and allows the detection of early transient actors of the classical pathway, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the first identified properties of native CRP was its ability to activate the complement cascade by sequestration of C1q. In previous studies on CRP-complement interactions, indirect techniques, such as hemolytic activity [14,15], enzyme immunoassays [37] or immunohistochemistry [38] have been used. In the present study, we chose null ellipsometry to analyze the CRP-mediated complement deposition onto model PC-surfaces, a method that is direct, non-destructive, quantitative and allows the detection of early transient actors of the classical pathway, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the complement cascade is regarded as one of the main physiological functions of CRP, originally described by Kaplan and Volanakis who demonstrated consumption of hemolytic complement components in acute-phase sera mixed with pneumococcal Cpolysaccharide, and by Siegel et al using CRP-protamine complexes [14,15]. In the presence of calcium, each CRP subunit is able to complex with a PC-containing structure.…”
Section: Introductionmentioning
confidence: 99%
“…The capacity of human CRP to bind to phosphocholine (11) and related residues that are widely present in bacteria and other pathogens, and then to precipitate soluble ligands, aggregate particulate ligands, and efficiently activate the classical complement pathway (12)(13)(14), all resemble closely the classical properties of Abs. Furthermore, there is direct evidence from model systems that CRP can protect against infection, specifically with strains of Streptococcus pneumoniae (15)(16)(17) and Haemophilus influenzae (18,19) that express phosphocholine appropriately.…”
mentioning
confidence: 99%
“…When CRP binds to an appropriate ligand in vitro, it can activate the complement system (8)(9)(10)(11)(12)(13). In the present study CRP was found bound to certain synovial nuclei in patients with rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 59%